SOCIAL AND PSYCHOLOGICAL FEATURES OF PROFESSIONAL CRISIS PERCEPTION BY HIGHER SCHOOL TEACHERS (Revista Inclusiones, 2020)
The relevance of the study lies in the objective changes (cultural, social, financial, etc.) in education in general and in higher education in particular, as well as by the changed position of the teacher in education. New working conditions, the misbalance of social roles, the inertness of the teachers’ selfawareness make the teachers reconsider their place in higher education, their role behavior, the need to build a new identity, as well as reconsider the features of the crisis. There are few studies of the system professional crisis of teachers caused by social transformations, which coincides and overlaps with the period of individual professional crisis. Obviously, the professional is supposed to react to the changed self-awareness, try to cope with the dissonance, and try to change. The present article aims to identify the socio-psychological features of the perception of the professional crisis by higher education teachers. Phenomenological approach is the major approach to the study of the problem. This approach makes it possible to comprehensively study such social and psychological features of the teachers’self-awareness as a success, self-realization, the image of oneself, one’s goals in life, as well as coping strategies.